2007
DOI: 10.1016/j.exger.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of plasma proteome in long-lived rats fed on a coenzyme Q10-supplemented diet

Abstract: Dietary coenzyme Q 10 prolongs lifespan of rats fed on a PUFAn-6-enriched diet.Our aim was to analyze changes in the levels of plasma proteins of rats fed on a PUFAn-6 plus coenzyme Q 10 -based diet. This approach could give novel insights into the mechanisms of lifespan extension by dietary coenzyme Q 10 in the rat. Serum albumin, which decreases with aging in the rat, was significantly increased by coenzyme Q 10 supplementation both at 6 and 24 months. After depletion of the most abundant proteins by affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…Interestingly, a significant number of protein changes identified in this work as the result of consumption of the VOO in comparison with the SO diet were also highlighted in a previous study focused on changes induced by dietary CoQ 10 supplementation of a diet containing SO compared to an SO alone diet (Santos-González et al 2007). The fact that a VOO diet and a CoQ 10 -supplemented SO diet increase the levels of proteins, such as serine protease inhibitor III, apolipoprotein A-I, or vitamin D binding protein, and decrease other proteins, such as hemopexin, prepohaptoglobin, fibrinogen gamma chain, alpha-2-HS glycoprotein, type II peroxiredoxin, inter-alpha inhibitor H4P heavy chain, or apolipoprotein H, when compared with the SO alone diet indicates that CoQ 10 and VOO may have similar effects on processes related to inflammation, blood coagulation, lipid metabolism, transport, and bone metabolism.…”
Section: Effects Of Dietary Oils On Coagulation and Hemostatic Processessupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, a significant number of protein changes identified in this work as the result of consumption of the VOO in comparison with the SO diet were also highlighted in a previous study focused on changes induced by dietary CoQ 10 supplementation of a diet containing SO compared to an SO alone diet (Santos-González et al 2007). The fact that a VOO diet and a CoQ 10 -supplemented SO diet increase the levels of proteins, such as serine protease inhibitor III, apolipoprotein A-I, or vitamin D binding protein, and decrease other proteins, such as hemopexin, prepohaptoglobin, fibrinogen gamma chain, alpha-2-HS glycoprotein, type II peroxiredoxin, inter-alpha inhibitor H4P heavy chain, or apolipoprotein H, when compared with the SO alone diet indicates that CoQ 10 and VOO may have similar effects on processes related to inflammation, blood coagulation, lipid metabolism, transport, and bone metabolism.…”
Section: Effects Of Dietary Oils On Coagulation and Hemostatic Processessupporting
confidence: 59%
“…Animals and diets used here were as documented in previous works (Bello et al 2006;Santos-González et al 2007;Quiles et al 2010). Groups of ten male Wistar rats (Rattus norvegicus) initially weighing 80-90 g were housed under standard conditions and maintained on a 12-h light/12-h darkness cycle and at a temperature of 22±1°C.…”
Section: Animals Diets and Blood Samplesmentioning
confidence: 99%
“…Previous evidence showed that DNA damage plays a crucial role in the mechanisms of atherosclerosis (Bennett 2001), as well as other diseases related to aging. In the same line, studies carried out on rats fed with diets rich in polyunsaturated fatty acids demonstrated that CoQ supplements have a protective effect against oxidative damage (Thomas et al 1996;Santos-Gonzalez et al 2007). Thus, our findings demonstrate for the first time that the long-term consumption of the Med+CoQ diet induced less DNA damage in elderly subjects, with an intermediate effect for the Med diet, both diets producing less damage than the SFA diet.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, supplementation with exogenous CoQ has been shown to lead to an increase in the CoQ content of LDL, and a decrease of their peroxidizability (Stocker et al 1991;Thomas et al 1996). Studies in animal models have shown the protective effect of CoQ when supplemented in the diet (Bello et al 2005;Santos-Gonzalez et al 2007), in which supplementation attenuated oxidative alterations, with lower levels of DNA damage (Quiles et al 2004). However, to date there are no human studies, especially cross-randomized controlled trials, aimed to determine the antioxidant effects of CoQ during the postprandial phase associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins of homogenized PFC tissues were precipitated using chloroform and methanol [34]. Subsequently, samples (n = 4 in each group) were resuspended in lysis buffer, and were assayed for protein concentration using 2-D Quant Kit.…”
Section: Western Blotmentioning
confidence: 99%